Internet of things, threats, landscape, and countermeasures - Shiaeles, Stavros; Kolokotronis, Nicholas (Boca Raton : CRC Press, 2021)
"Internet of Things (IoT) is an ecosystem comprised of heterogeneous connected devices that communicate to deliver capabilities making our living, cities, transport, energy, and other areas more intelligent. This book delves into the different cyber-security domains and their challenges due to the massive amount and the heterogeneity of devices. This book introduces readers to the inherent concepts of IoT. It offers case studies showing how IoT counteracts the cyber-security concerns for domains. It provides suggestions on how to mitigate cyber threats by compiling a catalogue of threats that currently comprise the contemporary threat landscape. It then examines different security measures that can be applied to system installations or operational environment and discusses how these measures may alter the threat exploitability level and/or the level of the technical impact. Professionals, graduate students, researchers, academicians, and institutions that are interested in acquiring knowledge in the areas of IoT and cyber-security, will find this book of interest"--
Data protection and privacy issues of the internet of things / O. Gkotsopoulou and P. Quinn.
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things -- Security measures; LAW / Forensic Science; TECHNOLOGY / Manufacturing; COMPUTERS / Security / General